A Coupled Material Removal Model for Chemical Mechanical Polishing Processes. (28th October 2021) - Akbar, Wazir; Ertunç, Özgür
Abstract : Chemical mechanical polishing (CMP) is a process used to obtain planarized surfaces in microelectronic device manufacturing. The planarization is achieved by material removal from the wafer surface by synergistic effect of chemical and mechanical actions. The material removal rate (MRR) in chemical mechanical processes have a linear dependency on applied down pressure. However, some experimental studies have reported nonlinear relationship between MRR and applied pressure. The nonlinearity can be attributed to complex interactions among the wafer, pad, abrasive particles, and chemical agents in the slurry. Therefore, in modelling CMP processes, coupling of both the chemical and mechanical actions is imperative to provide insight into the nonlinear behavior of MRR, because treating the chemical effects only as a mere means of softening the wafer surface fails to explain the nonlinear behavior of MRR in silicon dioxide CMP. Here, we present a model that couples micro-contact mechanics with diffusion of slurry into the wafer and predict MRR in CMP of silicon dioxide. The model is validated with experimental results available in the literature. Moreover, the developed model may be used to explain the nonlinear increase in MRR of silicon dioxide with increasing applied pressure.